2015
DOI: 10.1016/j.neuropharm.2014.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Microglial priming and enhanced reactivity to secondary insult in aging, and traumatic CNS injury, and neurodegenerative disease

Abstract: Glia of the central nervous system (CNS) help to maintain homeostasis in the brain and support efficient neuronal function. Microglia are innate immune cells of the brain that mediate responses to pathogens and injury. They have key roles in phagocytic clearing, surveying the local microenvironment and propagating inflammatory signals. An interruption in homeostasis induces a cascade of conserved adaptive responses in glia. This response involves biochemical, physiological and morphological changes and is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
305
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(318 citation statements)
references
References 149 publications
(230 reference statements)
10
305
1
2
Order By: Relevance
“…For instance, aged rodents demonstrate increased expression of mRNA and protein markers of inflammation following LPS challenge (Kumar et al, 2013;Norden and Godbout, 2013;Norden et al, 2015aNorden et al, , 2015b. In addition to aging, similar priming effects have been reported in microglia from patients with neuropsychiatric disorders including traumatic brain injury (Fenn et al, 2014) and neurodegeneration (Norden et al, 2015a). Of note, primed microglia were less responsive to the effects of glutamate reuptake enhancing agent riluzole compared with unprimed microglia from younger individuals (Brothers al, 2013).…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 81%
“…For instance, aged rodents demonstrate increased expression of mRNA and protein markers of inflammation following LPS challenge (Kumar et al, 2013;Norden and Godbout, 2013;Norden et al, 2015aNorden et al, , 2015b. In addition to aging, similar priming effects have been reported in microglia from patients with neuropsychiatric disorders including traumatic brain injury (Fenn et al, 2014) and neurodegeneration (Norden et al, 2015a). Of note, primed microglia were less responsive to the effects of glutamate reuptake enhancing agent riluzole compared with unprimed microglia from younger individuals (Brothers al, 2013).…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 81%
“…Converging evidence indicates that the aged brain contains primed and/or senescent microglia (Dilger & Johnson, 2008; Harry, 2013; Mosher & Wyss‐Coray, 2014), which may contribute to age‐related cognitive deficits and altered brain function (Norden et al, 2015). Therefore, we sought to explore the effects of replacing these resident “aged" microglia with new cells, via administration and withdrawal of CSF1R inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Neurogenesis in the dentate gyrus (DG) was assessed via administration of the thymidine analogue bromodeoxyuridine (BrdU), which is incorporated into the DNA of dividing cells, as well as staining for doublecortin (DCX), a marker of newly born neurons. A decline in neurogenesis is commonly observed in aging, and studies have indicated that this decline is in part due to chronically activated microglia (Barrientos, Kitt, Watkins, & Maier, 2015; Norden et al, 2015). As a result, aged mice exhibit markedly reduced neurogenesis, as seen by decreased levels of BrdU + cells ( p  < 0.001, Figure 5b,d–e) and DCX staining ( p  < 0.001, Figure 5b,e–f) in the subgranular zone (SGZ) of the DG compared to young mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, one study that also investigated neuronal white matter integrity found that levels of microglial activations correlated with structural changes in the brain 63 . Recent reviews detailing this dysregulated immune response in the brain following neurotrauma highlight the phenomenon of microglial priming as a key component of this harmful pro-inflammatory state 28,29,49 . In short, priming refers to microglia that are in a hypersensitive and hyperactive state; they are "primed" for a future exaggerated response to an internal or external challenge.…”
Section: Immunological Perspectives Of Tbi Sequelaementioning
confidence: 99%